Social norm and giving with indivisibility of money : an experiment on selfishness, equity, and generosity - Bao, Te (2020)
We study a dictator game considering selfishness, equity, and generosity. The dictators first indicate their willingness to give on a decision form and then allocate 10 yuan cash to the receiver in an envelope. The cash consists of 10 banknotes of 1 yuan in treatment 1 (high divisibility) and 2 banknotes of 5 yuan in treatment 2 (low divisibility). Treatment 2 only has three choices of giving.0;5;10/. 30% of individuals take ceilings or floors rather than the standard rounding in treatment 2. However, the individual roundup and rounddown behaviors cancel each other at the aggregate level.